Crop productivity, nutrient uptake and soil fertility as influenced by cropping system and fertilizers in pigeonpea (Cajanus cajan)-wheat (Triticum aestivum) cropping system - SHIVRAN, D R; AHLA WAT, I P S (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during 1997-99 at New Delhi on sandy loam soil to study the nutrient managementin pigeonpca [Cajanus cajan (L) Millsp] - wheat (Triticum aestivum L emend. Fiori & Paol.) system. The fertilizerapplication at 100% of the recommended dose to rainy season crops recorded the highest yield of pigeon pea. Wheat afterpigeonpea+blackgram (Phaseolus mungo L.) (stover incorporated) intercropping recorded markedly higher yield comparedwith the wheat after sole pigeon pea and pigeonpea+blackgram (stover removed) intercropping. Application of fertilizersup to 75% of the recommended dose to preceding rainy season crops and directly to wheat gave significantly higheryields of wheat over control. The cropping systems in respect of N, P, K and S uptake were in the following order: Pigeonpea+blackgram (stover removed )wheat>pigeonpea+blackgram (stover incorporated)-wheat>pigeonpea-wheat. The uptake of nutrients (N, P, K and S) increased up to 100 and 75% of recommended dose of fertilizers applied to rainy season crops and wheat, respectively. The pigeonpea+blackgram (stover removed) intercropping system recorded higher total N and available P in soil after rainy season crops compared with the sole pigeonpea. Application of fertilizers to rainy season crops up to 75% of the recommended dose improved total N, available P and S status of soil after rainy season crops over no fertilizer. The pigeonpea+blackgram (stover removed or incorporated)-wheat systems left behind higher available P in soil compared with pigeonpea-wheat system. The pigeonpea+blackgram (stover incorporated)wheatcropping system and fertilizer application to each crop in the system. recorded higher number of bacteria in soil.